Peran edukasi terstruktur dalam program discharge planning untuk meningkatkan efikasi diri pada pasien bedah jantung: A systematic review - Nisaa, Mariani; Nurachmah, Elly; Maria, Riri; Waluyo, Agung; Adam, Muhamad (Holistik Jurnal Kesehatan, 2025)
Background: Patients undergoing cardiac surgery often experience decreased self efficacy in managing their health condition, which can complicate recovery and reduce quality of life. Structured discharge planning programs provide ongoing support and instruction, which can help patients improve this self-efficacy. Purpose: To examine the role of structured education within discharge planning programs in improving self-efficacy in cardiac surgery patients. Method: This systematic review used PRISMA guidelines and included data published between 2020 and 2025 from the following databases: PubMed (n = 404), Science Direct (n = 24), ClinicalKey for Nursing (n = 769), Sage Journals (n = 47), ProQuest (n = 1063), and Wiley (n = 97). Results: Nine of the ten studies showed that patients who received structured discharge planning interventions, whether through direct instruction, technology (phone, WhatsApp, and augmented reality/AR), or home care, had higher levels of self efficacy. Furthermore, this intervention reduced readmission rates, depression, anxiety, and fatigue. Conclusion: A structured discharge planning program is effective in improving patient self efficacy after cardiac surgery and provides additional benefits on psychological aspects and quality of life. This program can be consistently implemented in patients undergoing cardiac surgery. Suggestion: Further research should be conducted in hospitals in Indonesia to determine the success of structured discharge planning in improving the self efficacy of cardiac surgery patients by linking local culture, family roles, and health systems.   Keywords: Cardiac Surgery; Discharge Planning Program; Patients; Self Efficacy; Structured Education.   Pendahuluan: Pasien yang menjalani operasi jantung sering mengalami penurunan efikasi diri dalam mengelola kondisi kesehatan pasien sendiri, yang dapat mempersulit pemulihan dan menurunkan kualitas hidup. Program rencana pemulangan terstruktur memberikan dukungan dan instruksi yang berkelanjutan, dapat membantu pasien meningkatkan efikasi diri. Tujuan: Untuk mengkaji peran edukasi terstruktur dalam program discharge planning untuk meningkatkan  efikasi diri pada pasien bedah jantung. Metode: Penelitian systematic review menggunakan pedoman PRISMA, diterbitkan dari tahun 2020-2025 dari database: PubMed (n = 404), Science Direct (n = 24), ClinicalKey for Nursing (n = 769), Sage Journal (n = 47), ProQuest (n = 1,063), dan Wiley (n = 97). Hasil: Sembilan dari sepuluh penelitian menunjukkan, bahwa pasien yang menerima intervensi discharge planning terstruktur baik melalui instruksi langsung, teknologi (telepon, WhatsApp, dan Augmented Reality/ AR), atau home care mempunyai tingkat efikasi diri yang lebih tinggi. Selain itu, intervensi ini mengurangi jumlah rawat inap ulang, depresi, kecemasan, dan kelelahan. Simpulan: Program discharge planning dengan edukasi terstruktur efektif dalam meningkatkan efikasi diri pasien pascaoperasi jantung dan memberikan manfaat tambahan pada aspek psikologis dan kualitas hidup. Program ini dapat menjadi implementasi pada pasien yang menjalani operasi jantung secara konsisten. Saran: Penelitian lebih lanjut harus dilakukan di rumah sakit di Indonesia untuk mengetahui keberhasilan discharge planning terstruktur dalam meningkatkan efikasi diri pasien bedah jantung dengan mengaitkan budaya lokal, peran keluarga, dan sistem kesehatan.   Kata Kunci: Bedah Jantung; Edukasi Terstruktur; Efikasi Diri; Pasien; Program Discharge Planning.